Strategies and Bottlenecks in Hexaploid Wheat to Mobilize Soil Iron to Grains - Kumar, Anil; Kaur, Gazaldeep; Singh, Palvinder; Meena, Varsha; Sharma, Shivani; Tiwari, Manish; Bauer, Petra; Pandey, Ajay Kumar (Frontiers in Plant Science, 2022)
Our knowledge of iron (Fe) uptake and mobilization in plants is mainly based on Arabidopsis and rice. Although multiple players of Fe homeostasis have been elucidated, there is a significant gap in our understanding of crop species such as wheat. It is, therefore, imperative not only to understand the different hurdles for the Fe enrichment in tissues but also to address specifically the knowns/unknowns involved in the plausible mechanism of Fe sensing, signaling, transport and its subsequent storage in plants. In the present review, a unique perspective has been described in the light of recent knowledge generated in wheat, an economically important crop. The strategies to boost efficient Fe uptake, transcriptional regulation, and long-distance mobilization in grains has been discussed, emphasizing recent biotechnological routes to load Fe in grains. This article also highlights the new elements of physiological and molecular genetics that underpins the mechanistic insight for the identified Fe-related genes at various levels and discus the bottlenecks in unloading the Fe in grains. The information presented here will provide much-needed resources and directions to overcome challenges and design efficient strategies to enhance the Fe density in wheat grains.